Male Genetic Evaluation in Infertility, Recurrent Abortion and Recurrent in Vitro Fertilization Failure; A Clinical Approach - Akhavizadegan, Hamed (Urology Journal, 2024)
Purpose: This review presents a clinical approach to genetic issues in male infertility. Unlike other related reviews that discuss different types of genetic diseases (such as Klinefelter and Down syndrome), this review focuses on the clinical features that result from these genetic problems (such as azoospermia and oligospermia). Methods: A narrative review of the clinical literature in PubMed was conducted using keywords related to male infertility, recurrent pregnancy loss, recurrent in vitro fertilization failure, and genetics. The search included articles with English reviews published online after 2020. Headlines were defined based on the available literature, and after a critical review of each manuscript, clinical facts were classified under the corresponding headlines, and a primary draft was written. Results: 29 relevant articles were selected from the search. According to the literature, there are clinical genetic approaches for azoospermia, severe oligospermia, severe teratospermia, severe asthenospermia, recurrent miscarriage, and recurrent in vitro fertilization failure. Conclusion: Although many mutations that can affect male fertility and spermogram have been identified, only a few have clinical predictive value.